Promoting Sales Growth through Digital Marketing Initiatives: Case Studies and Best Practices - Saikia, Moammad Darpana (Journal of Global Economy, Business and Finance, 2024)
Over the last fifteen years, digital media platforms have revolutionized marketing by providing new ways to reach, inform, interact, sell to, and serve customers. According to research, people now spend more than six hours every day online, across several devices. In the context of rising digital engagement, brands need to be prominently displayed across digital media in order to interface with their target audience. This paper attempts to delineate the aspect of digital marketing in this scenario for driving sales in organizations through digital marketing initiatives. Several existing techniques are explored, and best strategies are suggested by drawing upon opposite case studies to drive revenue growth and the organization's success.